2008
DOI: 10.1186/1746-4269-4-26
|View full text |Cite
|
Sign up to set email alerts
|

Ethnopharmacological survey of six medicinal plants from Mali, West-Africa

Abstract: An ethnopharmacological survey was carried out to collect information about the use of six medicinal plants in the regions around Siby and Dioila, Mali. The plants investigated were Biopyhtum petersianum, Cola cordifolia, Combretum molle, Opilia celtidifolia, Parkia biglobosa and Ximenia americana.More than 60 medical indications were reported for the use of these plants in traditional medicine. The most frequently reported ailments were malaria (25.6%), different types of pain (14.0%) and dermatitis (7.4%). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 29 publications
1
70
1
1
Order By: Relevance
“…The stem bark and leaf of African locust bean tree are used traditionally for the treatment of malaria [4,25]. In vivo and in vitro antiplasmodial activities of leaves of P.biglobosa had already been evaluated by Builders et al [12], studies on the efficacy of the stem bark of this important medicinal plant had already been reported by Builders et al [20], and also anti-inflammatory and analgesic activities of this plant had been reported by Kouadio et al [26].…”
Section: Discussionmentioning
confidence: 99%
“…The stem bark and leaf of African locust bean tree are used traditionally for the treatment of malaria [4,25]. In vivo and in vitro antiplasmodial activities of leaves of P.biglobosa had already been evaluated by Builders et al [12], studies on the efficacy of the stem bark of this important medicinal plant had already been reported by Builders et al [20], and also anti-inflammatory and analgesic activities of this plant had been reported by Kouadio et al [26].…”
Section: Discussionmentioning
confidence: 99%
“…Despite wide use of C. molle as medicinal plant for treatment of various ailment including helminthic, protozoal, bacterial and other infectious diseases in different parts of Africa (McGaw et al, 2001;Fyrquist et al, 2002;Bussmann et al, 2006;Grønhaug et al, 2008), studies conducted on its in vivo toxicity test is scanty. According to the traditional practice of the local community, the seed of the plant is used after it is extracted by water as a solvent.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In fact, preparation of plant-based remedies at the household level is often seen as a self-help measure. However, our recent field experiences with Psidium guajava (guava) leaf decoction (PGLD) as an antidiarrheal remedy revealed that preparation of a home-based remedy could be a limiting factor toward use of local medicinal plants.…”
Section: Dear Editormentioning
confidence: 99%